Afrique du Sud : Les enjeux du gaz de schiste - François Lafargue (VertigO)
The South-Africans have undergone regularly for several years of the interruptions of distribution of electricity, caused by the big rise of the request, which was not correctly anticipated and by the outdatedness of the installations. The public authorities which wish to reduce the use of the coal ore consider the exploitation of schist gas reserves, considered to be very promising. This article points out the delicate energy situation of the country, then presents the interest and the limits of such an exploitation of nonconventional gas in South Africa. Is the schist gas a solution with the energy challenge of the country and which price?